Cost Reduction and Sustainable Business Practices; A conceptual approach - Bello, Dikko (Journal of Economics and Administrative Sciences, 2020)
An excellent reputation earned by initiating and practicing sustainable business practices has additional benefits, of which are reducing environmental incidents and an improvement in operational efficiency as this has the potential to help firms improve on productivity and bring down operating costs. Taken further, with ever-increasing socially and environmentally-conscious investors and the public alike, this act of natural resources management could have a significant implication on market value and income of the practicing firms.The above proposition has been supported by sustainable business practices literature that is continuously conversing and deliberating upon the impact of efficient resource deployment and sustainable business practices.  This paper aims to add value and contribute by offering inferences on cost reduction possibilities through improved natural resources management. Therefore it is an entirely conceptual level approach that provided potentially efficient tools for business sustainability and profitability